The development of political attitudes and identities in Scotland and Britain - Macfarlane, E (2024)
This thesis assesses developments in political attitudes and identities in Scotland and Britain in the context of a changing and more volatile electorate. Using British Election Study data from 2014-2021, it contains four papers addressing different elements of changing political attitudes and identities over a period of turbulent politics. The thesis examines how identities are formed and the consequences of identities for the perception of politics.